2018
DOI: 10.1096/fasebj.2018.32.1_supplement.747.20
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of NHE2 Enhances Migratory Speed in Colonic Epithelial Cells

Abstract: BackgroundThe maintenance of epithelial function and barrier integrity is achieved by continuous renewal of the colonic epithelium through proliferation, migration and differentiation. Sodium hydrogen exchanger 2 (NHE2) is highly expressed in the colonic epithelium, where it is involved in Na+/H+ exchange, water absorption and pHi regulation. However, NHE2 deficiency in mice does not result in diarrheal phenotype. NHE2 is expressed in the cryptal region, where colonocytes exit the stem cell niche and migrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The failed reestablishment of the tight junctions post injury, especially disrupted occludin and claudin-1 localization patterns in the nhe2 −/− tissue, was offered as a mechanistic explanation ( Moeser et al, 2008 ). Our group has used Caco2BBe cells to address the impact of NHE2 on epithelial restitution, and we found that Caco2BBe cells upon “wounding” of the monolayer exhibit “sheet” migration, which is significantly increased in Caco2BBe cells with downregulated NHE2 expression ( Nikolovska et al, 2018 ). In our model we have shown that the lack of NHE2 in Caco2BBe cells leads to a significant decrease of the intracellular pH i ( Yu et al, 2019 ; Zhou et al, 2021 ; Nikolovska et al, 2022 ), which might influence the generation of the tight junction network or different signaling pathways and therefore affect cell migration.…”
Section: Nhe2 In the Gastrointestinal Tractmentioning
confidence: 99%
“…The failed reestablishment of the tight junctions post injury, especially disrupted occludin and claudin-1 localization patterns in the nhe2 −/− tissue, was offered as a mechanistic explanation ( Moeser et al, 2008 ). Our group has used Caco2BBe cells to address the impact of NHE2 on epithelial restitution, and we found that Caco2BBe cells upon “wounding” of the monolayer exhibit “sheet” migration, which is significantly increased in Caco2BBe cells with downregulated NHE2 expression ( Nikolovska et al, 2018 ). In our model we have shown that the lack of NHE2 in Caco2BBe cells leads to a significant decrease of the intracellular pH i ( Yu et al, 2019 ; Zhou et al, 2021 ; Nikolovska et al, 2022 ), which might influence the generation of the tight junction network or different signaling pathways and therefore affect cell migration.…”
Section: Nhe2 In the Gastrointestinal Tractmentioning
confidence: 99%